Analysis of Ecological Flow Threshold in Channel of the Tabu River Basin Based on Improved Intra-annual Distribution Method - QI Qingqing; FAN Panpan; ZHANG Zezhong; YIN Hang; ZHANG Weijie (Renmin Zhujiang)
The ecological environment of the Tabu River Basin is fragile, with frequent occurrences of desertification, vegetation degradation, and water body shrinkage, which seriously threaten the stability of the local ecosystem. In this context, ecological water replenishment represents a key measure for restoring its ecological functions, as it directly affects the restoration of river habitats, the maintenance of biodiversity, and the enhancement of regional ecological resilience. Basin's ecological water demand serves as a vital factor in maintaining ecological balance, which not only determines the rational allocation of water resources but also provides a scientific basis for formulating ecological protection policies. Therefore, conducting a scientific analysis of the ecological water demand at the Xichang Hanying section of the Tabu River contributes to safeguarding the health of the river ecosystem and promoting the sustainable development of the basin, which is of great practical significance. Based on the monthly measured runoff data from 1959 to 2016 at the Xichang Hanying Hydrological Station in the Tabu River Basin (this data has a long time series and contains rich hydrological information), the original data was first sorted and preprocessed, and outliers caused by human activities and natural disasters were eliminated to ensure the accuracy and reliability of the data. On this basis, the calculation process of this method was optimized to deal with the defect that the traditional intra-annual distribution method ignores the differences in ecological water demand in different hydrological periods. The study used the improved intra-annual distribution method to calculate the basic in-channel ecological flow at this section. To verify the effectiveness and superiority of the improved method, its calculation results were compared with those calculated by the traditional intra-annual distribution method and other commonly used hydrological methods (such as the frequency curve method, the minimum monthly average flow method, and the Qp method). At the same time, combined with the improved Tennant method evaluation criteria which are more applicable to seasonal rivers, the calculation results were evaluated. The results show that there is a significant difference in the evaluation results between the improved intra-annual distribution method and the intra-annual distribution method. The intra-annual distribution method is mostly rated as "very poor" in the monthly evaluations, which cannot meet the basic needs of the river ecosystem. In contrast, the improved intra-annual distribution method, which takes into account the actual ecological conditions of the basin, performed excellently in the evaluation: it reached the "excellent–optimal state" in January, February, July, November, and December, reached the "optimal state" in August, showed "very good–excellent" in July, and was mostly rated as "poor–medium" in the remaining months. Its overall performance is significantly better than that of the intra-annual distribution method and than some other commonly used hydrological methods in terms of adaptability.